Health service COVID-19 wellbeing and support initiatives: a mixed-methods evaluation. (11th July 2022) - Holton, S; Wright, A; Wynter, K; Hall, L; Wintle, J; Lambis, E; Cooke, L; McNally, C; Pavlovski, M; Bruce, S; Rasmussen, B
Abstract: Background: Health services implemented a range of initiatives during the COVID-19 pandemic to support employee wellbeing and assist employees to manage the professional and personal challenges they experienced. However, it is not known if such initiatives were acceptable to employees or met their needs. Aims: To evaluate the wellbeing and support initiatives implemented at an Australian health service during the COVID-19 pandemic from the perspectives of employees (both users and non-users) and key stakeholders. Methods: A mixed-methods design (survey, interviews and data audit) to investigate employees' and key stakeholders' perceptions, experiences and use of the wellbeing and support initiatives implemented at a large tertiary metropolitan health service in Melbourne, Australia. Results: Ten employees participated in an interview and 907 completed a survey. The initiatives were well used and appreciated by staff. There was no significant difference in the proportion of clinical staff who had used the initiatives compared to non-clinical staff (44% versus 39%; P =0.223). Survey respondents reported the initiatives improved their mental health ( n = 223, 8%), ability to cope with COVID-19 related stress and anxiety ( n = 206, 79%), do their work ( n = 200, 77%) and relationships with colleagues ( n = 174, 67%). Staff would like many of the initiatives (with some modifications) to continue after the COVID-19 pandemic. Conclusions: The findings suggest a high level of staff satisfaction with the implemented wellbeing and support initiatives, and confirm the need for, and importance of, developing and implementing initiatives to support health service staff during outbreaks of infectious diseases such as the COVID-19 pandemic.